2015
DOI: 10.1371/journal.pone.0123249
|View full text |Cite
|
Sign up to set email alerts
|

IMPIPS: The Immune Protection-Inducing Protein Structure Concept in the Search for Steric-Electron and Topochemical Principles for Complete Fully-Protective Chemically Synthesised Vaccine Development

Abstract: Determining immune protection-inducing protein structures (IMPIPS) involves defining the stereo-electron and topochemical characteristics which are essential in MHC-p-TCR complex formation. Modified high activity binding peptides (mHABP) were thus synthesised to produce a large panel of IMPIPS measuring 26.5 ±3.5Å between the farthest atoms fitting into Pockets 1 to 9 of HLA-DRβ1* structures. They displayed a polyproline II-like (PPIIL) structure with their backbone O and N atoms orientated to establish H-bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 103 publications
(165 reference statements)
3
52
0
Order By: Relevance
“…That goal was achieved when a large number of highly immunogenic protection-inducing peptide structures (IMPIPS) [13] fulfilled those requirements when used as individual epitopes in primary challenges.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…That goal was achieved when a large number of highly immunogenic protection-inducing peptide structures (IMPIPS) [13] fulfilled those requirements when used as individual epitopes in primary challenges.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…600 MHz spectrometer 1 H-NMR 3D structures were determined with RP-HPLC-purified IMIPS; their sequential connectivities and dihedral angles have already been described [13,14,16,17,18,19] . Only χ1 angle degrees of residues considered TCR contacting (positions p2, p5, p8) regarding their binding in the HLA-DR peptide binding region (PBR) are described, based on their predicted binding to HLA-DR molecules.…”
Section: Determining 3d Structurementioning
confidence: 99%
“…cHABPs having short, compact or right-handed a-helical structure with 1.5 A per residue, 3.6 residues per pitch (~12 A between the 9 residues the PBR can accommodate), inter-atomic H-bonds and f = -60 , -90 , y = -40 , -60 angle limits did not fit into the HLA-DRb1*PBR groove. Furthermore, cHABPs having long, extended structure b-sheets, folded b-turns (having 2 residues per turn and H-bonds between i + 1 and i + 2) or random structures were too long or had inadequate structure to fit into the HLA-DRb1*PBR [81, [100][101][102]. It has been reported that endogenous or variable antigenic peptides associated with HLA-DRb* alleles adopt a PPII L conformation and become firmly anchored into their PBR [100].…”
Section: Mhabp Structure--function Relationshipmentioning
confidence: 99%
“…In fact, we have recently reported that a mixture formed by CSP-and MSP-1-derived mHABPs having such P3 and P7 rotamer orientation did not block, interfere or compete with or suppress the protective immune response induced by just Spz-or Mrz-derived mHABPs, which we have called immune protection-inducing protein structures (IMPIPS) and should be the subunit components of any new chemically synthesised vaccine [81,102].…”
Section: Components For a New Antimalarial Vaccinementioning
confidence: 99%
See 1 more Smart Citation